2021
DOI: 10.1016/j.brs.2020.11.005
|View full text |Cite
|
Sign up to set email alerts
|

No effect of anodal tDCS on motor cortical excitability and no evidence for responders in a large double-blind placebo-controlled trial

Abstract: Background: Transcranial direct current stimulation (tDCS) has emerged as a non-invasive brain stimulation technique. Most studies show that anodal tDCS increases cortical excitability. However, this effect has been found to be highly variable. Objective: To test the effect of anodal tDCS on cortical excitability and the interaction effect of two participant-specific factors that may explain individual differences in sensitivity to anodal tDCS: the Brain Derived Neurotrophic Factor Val66Met polymorphism (BDNF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
41
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 50 publications
6
41
1
Order By: Relevance
“…Even though TDCS induced MEP changes have been replicated various times (for review Nitsche and Paulus, 2011), many recent reports, including a large doubleblind, placebo-controlled trial, did not show significant effects of anodal TDCS on corticospinal excitability. These recent studies consistently found that the individual change in MEP amplitude was highly variable (Horvath et al, 2014;Lopez-Alonso et al, 2014;Wiethoff et al, 2014;Chew et al, 2015;Strube et al, 2016;Ammann et al, 2017;Lefebvre et al, 2019;Jonker et al, 2020). The number of participants displaying the "classical" anodal TDCS-induced increase ranging only between 30 and 50%, while the other participants showed no or the opposite effect (Lopez-Alonso et al, 2014;Wiethoff et al, 2014).…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…Even though TDCS induced MEP changes have been replicated various times (for review Nitsche and Paulus, 2011), many recent reports, including a large doubleblind, placebo-controlled trial, did not show significant effects of anodal TDCS on corticospinal excitability. These recent studies consistently found that the individual change in MEP amplitude was highly variable (Horvath et al, 2014;Lopez-Alonso et al, 2014;Wiethoff et al, 2014;Chew et al, 2015;Strube et al, 2016;Ammann et al, 2017;Lefebvre et al, 2019;Jonker et al, 2020). The number of participants displaying the "classical" anodal TDCS-induced increase ranging only between 30 and 50%, while the other participants showed no or the opposite effect (Lopez-Alonso et al, 2014;Wiethoff et al, 2014).…”
Section: Introductionmentioning
confidence: 71%
“…MEP measurements are strongly dependent on the investigator holding the coil, even if neuro-navigation and other standard methods are applied. Knowledge about the session type might lead the experimenter to unconsciously influence study outcome and thereby artificially increasing the effect size and studies with a similarly rigorous design have also not shown effects of anodal TDCS on corticospinal excitability, even at significantly higher stimulation intensities (2 mA) (Jonker et al, 2020). A limitation of this study was that mean MEP amplitudes at pre-TDCS baseline were not matched between the real and sham TDCS conditions.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…For this reason, a replication of the protocol within a similarly controlled sample would be highly beneficial for the field, specifically with consideration of the impact of excluding all MEPs under 50 mV. Because this study largely challenges two decades of tDCS work (including many failed attempts to find any effect of tDCS on MEP amplitude; see [9] for a recent example using 2 mA tDCS), I hope that it receives the attention it deserves from the brain stimulation community.…”
mentioning
confidence: 99%